Intergenerational caregiving on mental health of middle-aged and older adults in China: empirical insights - Yan, Xueling; Wu, Wenjing; Chen, Xiaoqin; Xu, Guangming; Yu, Shule; Li, Shen (Frontiers in Public Health, 2023)
The impact of intergenerational caregiving on the mental health of providers remains a controversial topic, especially in countries like China where it is prevalent. Given the country's aging population and recent liberalization of the two-child policy, understanding the effects of intergenerational caregiving on the mental health of middle-aged and elderly individuals is crucial. Using data from the China Health and Aging Tracking Survey (CHARLS) 2013, this study aimed to explore the impact of intergenerational caregiving on mental health among middle-aged and elderly individuals. There is a significant positive effect of intergenerational care on the mental health of middle-aged and elderly people. Additionally, we re-profiled intergenerational care variables by considering the number and length of intergenerational caregivers, and found that the effects remained significant. Furthermore, the effects of intergenerational care vary across subgroups based on gender, age, nature of usual residence, marital status, and physical health status. Finally, we identified two mechanisms through which intergenerational caregiving positively affects mental health: intergenerational financial support and intergenerational spiritual support. These findings have important implications for policymakers, healthcare professionals, and family members in promoting the mental health of middle-aged and elderly individuals in China.